NUMERICAL INVESTIGATION OF PREMATURE FATIGUE OF HIGH-SPEED TRAIN WHEELS IN PRESENCE OF FACETS DEFECT WITH CASE STUDY - Jouilel, Naima; Mhaiti, Nissrine; Radouani, Mohammed; El Fahime, Benaissa (Journal of Applied Engineering Science, 2023)
In this paper, the premature failure of the high speed railway wheel of power locomotive commissioned in Morocco since 2018 was investigated. A three dimensional model of the wheel is established, with account of specific wheel’s features, to perform the finite elements and modal analysis. Simulations were conducted for several functional diameters of wheels (850mm, 885mm, and 920mm) to figure out stress distribution in different operation conditions. Stress results show that the wheel bears the mechanical loading in both exceptional and fatigue loads, therefore a modal analysis of the structure in presence of facets, which create a vibratory state, is done to examine their effect on the premature fatigue of the wheel. Modal analysis reveals that the presence of facets leads to a vibratory mode near to resonance. Based on those results, critical operation points as function of facets number and wheel diameter were determined to avoid scenarios that lead to cracks and premature fatigue of the studied wheels. Existing maintenance procedures must be modified to overcome this problem and increase the wheel’s lifetime without affecting the operation safety of the high-speed train.